Methods of experimental induction of periapical inflammation. Microbiological and radiographic evaluation - Tanomaru-Filho, M. [UNESP]; Poliseli-Neto, A. [UNESP]; Leonardo, M. R. [UNESP]; Silva, L. A B; Tanomaru, Juliane Maria Guerreiro [UNESP]; Ito, I. Y. (Wiley, 2005)
Aim: To evaluate the influence of coronal filling and apical perforation on the induction of periapical inflammation. Methodology: Fifty-eight root canals in the teeth of dogs were divided into four groups. Groups I and II: root canals were exposed for 180 days; groups III and IV: root canals were exposed for 7 days and then the access cavity filled for 53 days. The root apices of groups I and III were perforated after the coronal opening, whilst those of groups II and IV remained intact. Standard radiographs were taken before and after the experimental periods. Digital images of the radiographs were created and then analysed by three examiners. After induction of periapical inflammation, the root canal contents were collected using paper points. Microbiologic evaluation of the type of microorganism was carried out by culture in different growth media. The radiographic and microbiologic data were statistically analysed using ANOVA at a 5% significance level. Results: There were a greater total number of microorganisms in groups I and II (P < 0.05). The number of anaerobes was greater than the number of aerobes (P < 0.05). The size of the periapical radiolucencies were not significantly different between the experimental groups. Conclusions: The different methods analysed induced similar areas of periapical radiolucency in dogs with predominantly anaerobic bacteria. However, the time required for induction was less when the method with coronal filling was used. © 2005 International Endodontic Journal.
Keywords: Dental radiograph; Endodontics; Microorganism; Periapical inflammation; aerobic bacteria; anaerobic bacterium; animal model; animal tissue; bacterium culture; controlled study; dog; inflammation; microbiological examination; nonhuman; radiodiagnosis; statistical analysis; statistical significance; tooth filling; tooth periapical disease; tooth root; Analysis of Variance; Animals; Bacteria, Anaerobic; Bacteriological Techniques; Colony Count, Microbial; Dental Pulp Cavity; Dental Pulp Necrosis; Dental Research; Dogs; Periapical Periodontitis; Time Factors; Tooth, Nonvital